(3GdMOGFbs - (3GdOQGRj, GdHMQGfj, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje, J(B1186(3g`s ((3jhSa Hf MejOs)
(3ChdgG (B:s
(3cJGH GdML hgh jWdb aj GddZI Ydi eYGf ceG jSJaGO ef GdbGehS(B...s
(3BNQgG (B:s
...(3hYOe Gdbhd HeVehf GdQhGjI GdOGdI Ydi GdcaGQI eY UMJgG hUQGMJgG dG jhLH WQMgG hdG JChjdgG Hd GdhGLH GdYed HgG(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B8(3,U(B215s
(3GdPQjYI(B:(3L(B6(3,Qbe(B1557s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis